2021
DOI: 10.1155/2021/4616747
|View full text |Cite
|
Sign up to set email alerts
|

Undrained Cyclic Response and Resistance of Saturated Calcareous Sand considering Initial Static Shear Effect

Abstract: Sand elements in the natural or manmade field have often undergone initial static shear stresses before suffering cyclic loading. To explore the effect of static shear stress, a series of undrained cyclic triaxial tests were performed on dense and loose calcareous sand under different initial and cyclic shear stresses. The triaxial test results are used to describe the effect of static shear stress on the cyclic response of the calcareous sand with different relative density. Cyclic mobility, flow deformation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Li et al [16] studied the efect of static shear stress on the cyclic response of calcareous sand with diferent relative densities under cyclic loading. Tey showed that the cyclic resistance of dense sand is greater than that of loose sand, and it accumulated dissipated energy faster than loose sand.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al [16] studied the efect of static shear stress on the cyclic response of calcareous sand with diferent relative densities under cyclic loading. Tey showed that the cyclic resistance of dense sand is greater than that of loose sand, and it accumulated dissipated energy faster than loose sand.…”
Section: Introductionmentioning
confidence: 99%
“…As a kind of special unsaturated soil, gassy soil is widely distributed in coastal areas and alluvial plains. During the construction of subway, foundation pit, large sea crossing bridge, deep-water port wharf, and slope engineering in these areas [1][2][3], some engineering accidents have been caused due to the lack of understanding of the engineering mechanical properties of gassy soil [4][5][6][7][8]. Different from the general unsaturated soil, the gas in the gassy soil is in a closed state, that is, there are gas bubbles in the soil.…”
Section: Introductionmentioning
confidence: 99%